Pengaruh Viral Marketing, Celebrity Endorser dan Brand Image Terhadap Keputusan Pembelian Di Shopee (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Angkatan 2017 Universitas Islam Malang) - Puspita Nirmala Rihhadatul Aisy; M. Ridwan Basalamah; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine and analyze the effect of viral marketing, celebrity endorser and brand image on purchasing decisions on shopping applications at shopee. The population in this study are students of the Faculty of Economics and Business Class of 2017 Islamic University of Malang who have made purchases in the shopping application at shopee. The method of data collection used in this study was a questionnaire which was distributed to 80 respondents who were selected using purposive sampling. The independent variables consist of viral marketing, celebrity endorser and brand image while the dependent variable in this study is the purchase decision which is measured using multiple linear regression analysis. The results of the study simultaneously show that viral marketing, celebrity endorser and brand image have a positive and significant effect on purchasing decisions. Partially, viral marketing and brand image have a significant effect on purchasing decisions, while celebrity endorsers have no significant effect on purchasing decisions. Keywords : Viral Marketing, Celebrity Endorser and Brand Image, purchase decision.